UPAYA PENINGKATAN KUALITAS PEMBELAJARAN IPA DI MTS MUHAMMADIYAH 1 MALANG - Hindun, Iin; Wahyuni, Sri; Miharja, Fuad Jaya; Mashuri, Mashuri; Nurwidodo, Nurwidodo; Husamah, Husamah (JURNAL WIDYA LAKSANA, 2020)
This assistance aims to improve the quality of science learning in MTs Muhammadiyah 1 Malang. This assistance is motivated by the limitations of LS assistance services from tertiary institutions to elementary and secondary schools. Whereas learning innovations such as LS really need to be disseminated, maintained, strengthened, and improved in their field implementation so that the achievement of quality in learning is guaranteed. Assistance is carried out with the method of socialization, implementation, monitoring, evaluation and follow-up. Assistance was followed by a group of science teachers in Matsamutu and was conducted for one semester. The results of the mentoring, the socialization phase included the Matsamutu LS team in the MEPS, conducted socialization and assisted teachers in preparing lesson plans for 2 lessons, carried out an open plan with the model teacher from the school, implemented learning reflections and documented the results of the mentoring implementation and compiled collaborative publication articles. . It can be concluded that the assistance has provided benefits in increasing understanding of the procedures, principles of implementation, and scientific work resulting from the implementation of the LS